ONLINE FOOD TRADE AS A GROWTH DRIVER OF THE RUSSIAN E-COMMERCE MARKET - V. M. Tiunov (Современная наука и инновации, 2022)
The article is devoted to one of the rapidly developing areas in the Russian market of electronic industry - e-Commerce (electronic commerce). From English, e-Commerce is translated as electronic commerce this is the field of e-commerce, which includes the electronic sale and purchase of goods or services via the Internet, including the execution of such operations as online payments/transfers, etc. E-Commerce is the largest sector of the electronics industry and is based primarily on the technological advances of the semiconductor industry. During the period of coronavirus infection (COVID-19), which occurred in 2019, the growth of online sales, as well as the purchasing audience of e-Commerce in Russia, increased many times. This is primarily due to the epidemiological dangerous situation that was caused by the pandemic. In this regard, buying food via the Internet was the only way to protect your life. With the removal of restrictive measures, the growth of online sales according to experts of the Association of Internet trade companies (AKIT) in the first half of 2020 amounted to about 10,9 %, a significant contribution to which was made by the food delivery segment. In addition, according to AKIT forecasts, the online trading market will feel the effect of the pandemic until 2024. In the future, timesaving factors, convenience, and a service that will simplify their lives as much as possible will play an important role for customers when making purchases. Despite this, it is possible to identify some growth drivers for the development of online food trading. In this article, the author has identified the most significant growth drivers that can lead to a powerful push to promote online food sales.